Social-emotional Learning at the Foundational Stage - Chauhan, Namra (THE PRIMARY TEACHER, 2025)
Social-emotional Learning (SEL) is an essential skill for both children and adults, particularly during the foundational years of a child’s life, aged 3–8 years. This article explores what SEL looks like at this early stage and emphasises its importance for holistic development. It discusses strategies for integrating SEL practices into daily life for teachers, parents and caregivers who work with children. This article also discusses practical implications of the CASEL (Collaborative for Academic, Social and Emotional Learning) framework, emphasising activities that promote emotional expression, relationship management, empathy and effective communication. The objective of the article is to highlight the importance of early implementation of these skills and to offer insights for integrating SEL practices into daily interactions. By highlighting these approaches, the article encourages adults to foster children’s social-emotional development through meaningful actions.